Novel primers for mini-barcoding of seahorses for wildlife trade and seafood forensics - ELAH MARIE M. SALAMIDA; SHARON ROSE M. TABUGO (Society for Indonesian Biodiversity, 2026)
Abstract. Salamida EMM, Tabugo SRM. 2026. Novel primers for mini-barcoding of seahorses for wildlife trade and seafood forensics. Biodiversitas 27 (3): d270335. https://doi.org/10.13057/biodiv/d270335. Seahorses are charismatic fish facing increasing threats from habitat loss and the illegal wildlife trade. They are targeted and trafficked in the global market, further threatening their status. The high levels of both interspecific and intraspecific variability are also affecting the accuracy of species definition. Thus, this study developed a systematic pipeline for designing DNA mini-barcode primers using accessible software and integrated bioinformatics tools to enhance the detection of vulnerable seahorse species in wildlife trade and seafood forensics. The overarching goal is to support conservation efforts and promote the sustainable use of marine resources. DNA mini-barcodes, short sequences under 200 bp, show promise and can be useful for identifying species from degraded or processed samples. In this study, cytochrome b gene sequences—known for combining conserved and variable regions—were the basis for designing species-specific mini-barcode primers. These primers were tailored to improve molecular identification from low-quality seahorse samples, such as dried or frozen specimens commonly encountered in trade. Novel primers were initially evaluated using in silico Polymerase Chain Reaction (PCR), yielding four top-performing primer sets, which were subsequently validated by actual PCR. A total of nine Hippocampus spp. samples (four dried, five frozen) were used to test primer efficacy. PCR amplification and gel electrophoresis results confirmed that all primer sets successfully amplified DNA and produced good-quality PCR products. Sequencing data revealed accurate base-calling, with high percentage identity matches to reference sequences. These novel primers show potential for species identification in seahorse monitoring and enforcement contexts.